2002
DOI: 10.1023/a:1021604623208
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In this review, changes in brain lipid composition and metabolism due to aging are outlined. The most striking changes in cerebral cortex and cerebellum lipid composition involve an increase in acidic phospholipid synthesis. The most important changes with respect to fatty acyl composition involve a decreased content in polyunsaturated fatty acids (20:4n-6, 22:4n-6, 22:6n-3) and an increased content in monounsaturated fatty acids (18:1n-9 and 20:1n-9), mainly in ethanolamine and serineglycerophospholipids. Cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(41 citation statements)
references
References 64 publications
4
37
0
Order By: Relevance
“…More than one third of these lipids are very long chain polyunsaturated acids such as DHA and arachidonic acid (AA, 20:4 n-6) [23]. DHA is the most abundant n-3 FA in the mammalian central nervous system, specifically concentrating in lipid bilayer membranes of brain grey matter and retinal membranes [2425]. The incorporation of n-3 FA into neuronal membranes leads to increased membrane fluidity which can increase the number and affinity of receptors in synaptic regions and improve neurotransmission [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than one third of these lipids are very long chain polyunsaturated acids such as DHA and arachidonic acid (AA, 20:4 n-6) [23]. DHA is the most abundant n-3 FA in the mammalian central nervous system, specifically concentrating in lipid bilayer membranes of brain grey matter and retinal membranes [2425]. The incorporation of n-3 FA into neuronal membranes leads to increased membrane fluidity which can increase the number and affinity of receptors in synaptic regions and improve neurotransmission [26].…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of n-3 FA into neuronal membranes leads to increased membrane fluidity which can increase the number and affinity of receptors in synaptic regions and improve neurotransmission [26]. The levels of DHA in the brain increase during development [27] and decrease with aging [24]. When n-3- and n-6 FA-containing foods are consumed, n-3 and n-6 FA interact and may compete with each other in fatty acid metabolic pathways and in pathways of incorporation into cells, leading to varying levels in brain tissues and other organs [25].…”
Section: Introductionmentioning
confidence: 99%
“…Aging is a physiological process during which important changes occur in membrane lipid composition and metabolism, especially in the neural tissue [6,27]. The changes in LPP and DAGL enzymatic activities lead to a higher nuclear DAG availability in cerebellar nuclei from aged animals with respect to adults.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work carried out by our research group on different brain areas of aged rats demonstrated changes in lipid profile and metabolism with respect to adults. Some of these changes consisted in a different regulation of the enzymatic activities involved in DAG and phosphatidic acid (PA) production [6,7]. In addition, it was shown that insulin regulates PA/DAG balance in cerebral cortex synaptosomes and that this regulation also changes in aged animals [8].…”
Section: Introductionmentioning
confidence: 99%
“…Average fish intake of the general Dutch population as estimated in 1998 was only 10 g per day [122], especially in older men, of whom 28% did not consume fish at all and 41% consumed >20 g per day, but only 11% comprised fatty fish [123]. With aging, n–3 PUFA concentrations in brain tissues appear to decrease [124,125], and also, cognitively impaired and demented individuals have decreased blood levels of n–3 PUFA [126,127]. The underlying cause of these changes is largely unknown and could be related to inefficient conversion of precursors (linoleic acid and ALA) to long-chain PUFA or a high n–6 fatty acid intake and/or reduced n–3 PUFA intake, but also to impaired Δ-6 and Δ-5 desaturase activity or increased lipid peroxidation [116].…”
Section: N–3 Pufamentioning
confidence: 99%